Hybridization Silurids: An alternative for fish farming at high risk for the conservation of native species (Orinoquia, 2016)
The purpose of this article was to analyze, from a critical perspective, the risk that would be exposed some silurid species in captivity, subjected to hybridization processes for strictly commercial reasons, including habitat effects, competition and genetic erosion. It is easy to understand that these procedures will be in the future effects on aquatic resources, ecosystem services and food security, which can only be measured over time and not immediately.Keywords: Aquaculture; fitness; genetic erosion; native fish (aquatic resources).
Keywords: Aquaculture; fitness; genetic erosion; native fish (aquatic resources)